Research anthology on pediatric and adolescent medicine (Medical Information Science Reference, 2022)
"This book presents the developments, emerging technologies, and challenges in pediatric and adolescent medicine including adolescent health management and promotion as well as recent discoveries on childhood development through a variety of related issues such as media consumption, neuro-developmental disorders, and health promotion"--